2020
DOI: 10.3389/fbioe.2020.00795
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Traumatic Upper-Limb Peripheral Nerve Injuries Using Surface Electromyography

Abstract: Background: There is a great demand for convenient and quantitative assessment of upper-limb traumatic peripheral nerve injuries (PNIs) beyond their clinical routine. This would contribute to improved PNI management and rehabilitation. Objective: The aim of this study was to develop a novel surface EMG examination method for quantitatively evaluating traumatic upper-limb PNIs. Methods: Experiments were conducted to collect surface EMG data from forearm muscles on both sides of seven male subjects during their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It can provide expertise more conveniently and spread expert knowledge to primary healthcare providers. Tang et al ( 11 ) reported a quantitative assessment method for upper-limb traumatic PNI. In their study, the presence of radial, ulnar, or median nerve injury was identified under an expert system using the data of surface EMG with 81.82% sensitivity and 98.90% specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can provide expertise more conveniently and spread expert knowledge to primary healthcare providers. Tang et al ( 11 ) reported a quantitative assessment method for upper-limb traumatic PNI. In their study, the presence of radial, ulnar, or median nerve injury was identified under an expert system using the data of surface EMG with 81.82% sensitivity and 98.90% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis of nerve injury depends on clinical history, clinical symptoms, and physical and neurological examinations ( 7 , 8 ). Among the examinations, electromyography (EMG), nerve conduction studies (NCS), MRI, and high-resolution ultrasonography have been successfully used as diagnostic methods for PNI ( 9 11 ). However, these examinations are expensive, invasive, and rely on specialized equipment and professional operators, restricting their application in primary assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumentation complexities have hindered clinical uptake but use in research is gathering pace [209] and not only due to its painless nature. It provides many opportunities for gathering significant amounts of useful data, including longitudinal monitoring, wireless data capture, and muscle activation patterns [210,211].…”
Section: Surface Electrodesmentioning
confidence: 99%
“…For instance, EMG signals can reflect the activity and functional status of muscles, making them invaluable in clinical diagnostics and rehabilitation training within the neuromuscular system 4,5 . By examining EMG signals from affected areas, parameters such as denervation potentials and nerve conduction velocity can be obtained, aiding in assessing the extent of a nerve injury 6,7 . Additionally, in rehabilitation training, monitoring EMG signals provides quantitative information about muscle electromyographic output, assisting healthcare professionals in developing precise treatment and rehabilitation plans 8 .…”
Section: Introductionmentioning
confidence: 99%